Body Mass Index and Melanoma Prognosis - Nicoletta Cassano; Stefano Caccavale; Gino A. Vena; Giuseppe Argenziano (Mattioli1885, 2021)
Introduction: Obesity has been suggested as a risk factor in the progression of malignancies, including melanoma. Most studies defined obesity using body mass index (BMI), although the index is considered an imperfect measure of body composition. Objective: The aim of this article is to examine whether BMI can impact the prognosis of cutaneous melanoma, regardless of anti-tumor therapy. The relationship between BMI and specific prognostic factors in melanoma patients has been reviewed. Methods: Literature search was conducted on PubMed using the terms "melanoma" and "body mass index" or "obesity". We selected articles, published up to 30 November 2020, examining the prognostic aspects of melanoma. Articles evaluating the risk and incidence of melanoma were excluded as well as studies regarding morbidity and complications following surgical procedures, or those performed in metastatic melanoma patients treated with anti-tumor therapies. Results: Mixed results have emerged from studies assessing the clinical outcomes in melanoma patients in relation to BMI. More consistent data seem to support the relationship between BMI and Breslow thickness. Conclusions: Studies that focus specifically on the link between obesity and melanoma prognosis are limited; further research is needed to deepen our knowledge on this link.